Introduction to numerical programming a practical guide for scientists and engineers using Python and C/C++ /c Titus Adrien Beu - Beu, Titus A. (Series in computational physics, 2015)
This book introduces numerical programming using Python and C/C++, emphasizing methods used in physics and engineering. Its helps readers develop the ability to navigate relevant algorithms, knowledge of coding design, and efficient scientific programming skills. It requires minimal background in mathematics, leading readers from elementary methods to complex algorithms useful in modern programming